2017
DOI: 10.5152/eurasianjmed.2017.17218
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of the Unusual Presentations, Associations and Clinical Mimics of Acute Appendicitis

Abstract: There are many kinds of unusual presentations or associations and clinical mimics of acute appendicitis, and definitive diagnosis requires knowledge of the imaging findings in some cases. The unusual presentations and associations of acute appendicitis included in this study are perforated appendicitis, acute appendicitis occurring in hernias, acute appendicitis with cystic endosalpingiosis, intussusception of appendix, and acute appendicitis with pregnancy. We also present uncommon gastrointestinal, urinary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Ultrasound is typically the first radiologic evaluation for this presentation as it is a faster modality with high sensitivity for appendicitis and typhlitis [7], but considering further characterization of bowel inflammation on CT has been recommended when it does not significantly delay diagnosis. Bowel wall thickening and inflammation of the cecum detected by CT have been proposed as the main criterion to establish the diagnosis of typhlitis [2,4,5,[7][8][9]. The extent of bowel wall thickening is also a valuable prognostic factor, which adversely affects the outcome [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound is typically the first radiologic evaluation for this presentation as it is a faster modality with high sensitivity for appendicitis and typhlitis [7], but considering further characterization of bowel inflammation on CT has been recommended when it does not significantly delay diagnosis. Bowel wall thickening and inflammation of the cecum detected by CT have been proposed as the main criterion to establish the diagnosis of typhlitis [2,4,5,[7][8][9]. The extent of bowel wall thickening is also a valuable prognostic factor, which adversely affects the outcome [9].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment consists of IV antibiotics and bowel rest. Surgery is considered for complications related to necrosis [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…To note would be that in the 40ies, appendix bands were considered the background for familial acute appendicits, syndromicity being also mentioned (Downs, 1942; Gerster, 1915; Oelhafen, 2012). Intestinal obstruction as well as internal herniation, volvulus or, post‐stricture torsion necrosis may occur (Coughlin, 2010; Demir, 2017; Oelhafen, 2012; Singal, 2017). Knots or loops distinct from adhesions (post‐surgery, infectious), or peri‐ileal vitelline vascular remnants (Maeda et al, 2004) are also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Of note would be the persistence of difficulties in appendix surgery, as suggested by several, some recent, publications (Awari et al, 1995; Hedge and Hedge, 2008; Kacprzyk et al, 2020). Appendix bands, considered lesions of uncertain etiology (possibly congenital) may be detected in association with possibly life‐threatening complications such as appendix torsion, intestinal obstruction, and acute appendicitis and abdomen (Demir et al, 2017; Singal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of acute appendicitis in pregnancy has been reported to be 1:1250 and 1:1500 [8][9][10][11][12][13][14][15]. The possibility of acute appendicitis is higher in the second and third decades of life which are the fertility years [16][17][18].…”
Section: Introductionmentioning
confidence: 99%